INTERNET ADDICTION AMONG MADRASAH ALIYAH STUDENTS - Nursalamah Siagian; Nur Alia (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
The entry of new technology, the Internet, in people's lives demands adaptation by various groups, including students. With the use of the Internet by students, there will be changes in their lifestyle, which can affect their activities at school. This study focused on the intensity of internet use by students at Madrasah Aliyah (MA) Al Islamiyah Depok City, which then tend to become addicted to the Internet. This study used interview techniques, and the respondents were the Principal of Madrasah, teachers, and students. Document studies were also used to analyze case reports on internet use recorded by Guidance Counseling (BK) teachers. This study also used a questionnaire distributed online to 340 students at MA Al-Islamiyah Depok City. This study found that 14% of students access the Internet for more than 9 hours, 29% of students feel uncomfortable if they are not connected to the Internet, and 54% of respondents feel anxious if they run out of the internet quota, so they will immediately buy the quota. The impact of using the Internet intensively is that students are lazy to do other activities, such as playing with peers and forget about their duties and responsibilities, particularly studying. In addition, even when studying in class, they still use cell phones for social media and listening to music.